Lumbosacral pain in a patient with psoriatic arthritis: when the rheumatic disease is innocent - H. Parente; M. Pontes Ferreira; C. Soares; F. Guimarães; S. Azevedo; D. Santos-Faria; J. Tavares-Costa; D. Peixoto; C. Afonso; D. Roriz; F. Teixeira (PAGEPress Publications, 2023)
Lumbar pain is a very common symptom that derives from benign musculoskeletal conditions, rheumatic inflammatory diseases, neoplasms, and referred and/or nociplastic pain. A 70-year-old man with psoriatic arthritis presented with early-onset lumbosacral pain without evident red flags. Symptomatic treatment was unhelpful. Radiographic imaging showed subtle signs of a disease that could easily be missed. Magnetic resonance imaging revealed a massive prostatic malignancy with bone (sacral and iliopubic) metastasis. Awareness must be given not to disregard every lumbar pain as part of the preexisting rheumatic inflammatory disease (spondyloarthropathy in this case) or a common muscle/ligament/articular disarrangement. Persistence of pain, albeit not inflam-matory nor sharp in nature, despite adequate treatment might be just as important as an acute red flag and requires proper follow-up.